Imaging-Based Surrogate Markers of Transcriptome Subclasses and Signatures in Hepatocellular Carcinoma: Preliminary Results - Taouli, Bachir (Eur Radiol, 2017)
OBJECTIVES: In this preliminary study, we examined whether imaging-based phenotypes are associated with reported predictive gene signatures in hepatocellular carcinoma (HCC). METHODS: 38 patients (M/F 30/8, mean age 61 y) who underwent pre-operative CT or MR imaging before surgery as well as transcriptome profiling were included in this IRB approved single centre retrospective study. Eleven qualitative and 4 quantitative imaging traits (size, enhancement ratios, wash-out ratio, tumour-to-liver contrast ratios) were assessed by 3 observers and were correlated with 13 previously reported HCC gene signatures by using logistic regression analysis. RESULTS: 39 HCC tumours (mean size 5.7 ± 3.2 cm) were assessed. Significant positive associations were observed between certain imaging traits and gene signatures of aggressive HCC phenotype (G3-Boyault, Proliferation-Chiang profiles, CK19-Villanueva, S1/S2-Hoshida) with odds ratios ranging from 4.44–12.73 (P <0.045). Infiltrative pattern at imaging was significantly associated with signatures of microvascular invasion and aggressive phenotype. Significant but weak associations were also observed between each of enhancement ratios and tumour-to-liver contrast ratios and certain gene expression profiles. CONCLUSIONS: This preliminary study demonstrates a correlation between phenotypic imaging traits with gene signatures of aggressive HCC, which warrants further prospective validation to establish imaging-based surrogate markers of molecular phenotypes in HCC.